Differences in mechanical characteristics of vertical jump between athletes in sports games - Dokic, M.; Radenkovic, M.; Stankovic, R. (Facta Universitatis: Series Physical Education and Sport, 2018)
Vertical jump is one of the most common ways to evaluate the explosive power of lower extremities in athletes. For the development of explosive power, plyometric exercises are mostly used as a form of training. Participants were handball players (N=13), volleyball players (N=13) and basketball players (N=13) from city of Nis. They all competed in the highest state competition. After analyze all data conclusions are that the mechanical characteristics estimated by the accelerometer are statistically not significantly different in the examined athletes' groups except in the jump height and the kinematic characteristics of the vertical jump obtained by the video analysis statistically do not differ significantly, except in the variations of the angular velocity in the hip joint in the ankle.